Therapeutic exercise : moving toward function - Brody, Lori Thein; Hall, Carrie M. (Philadelphia : Wolters Kluwer, 2018)
The fourth edition of this text provides a conceptual framework for learning how to make clinical decisions regarding the prescription of therapeutic exercise, from deciding which exercise(s) to teach, to how to teach them, to the dosage required for the best possible outcome. Throughout this text, readers will learn how to treat, with the use of therapeutic exercise and related interventions, the impairments that correlate to functional limitations and the disability and to work toward the most optimal function possible
VII. CASE STUDIES ; -- APPENDIX 1: Red flags : recognizing signs and symptoms -- APPENDIX 2: Red flags: potentially serious symptoms and signs in exercising patients -- APPENDIX 3: 2016 PAR-Q +: The physical Activity Readiness Questionnaire for Everyone
Includes bibliographical references and index
Keywords: Exercise therapy; Exercise Therapy -- methods